Effects of biochar and Fe-modified biochar on acid buffering capacity and organic carbon fractions of lateritic red soil - Kaijie HU; Chenglong YU; Jiayi CHEN; Shufang CHEN; Yujin LIU; Hui WEI (Huanan Nongye Daxue xuebao)
ObjectiveLateritic red soil is a kind of acidic soil that covers a considerable proportion of the land in south China. Continuous soil acidification affects its physical and chemical property as well as biological characteristic, which is adverse to the maintenance of soil function as well as the accumulation and storage of soil organic carbon. Biochar addition could remedy the acidified soils effectively. This study was aimed to explore the impacts of biochar and Fe-modified biochar on the acid buffering capacity and organic carbon fractions of lateritic red soil, in order to provide a scientific basis for acid soil improvement as well as soil carbon sequestration and enhancement. MethodThis study focused on lateritic red soil as the research subject, with the addition of rice straw biochar and Fe-modified rice straw biochar prepared at different temperatures (300, 450, and 600 ℃). By measuring indicators such as soil pH, acid buffering capacity, total organic carbon content, aggregate organic carbon content, and dissolved organic carbon content, the effects of biochar addition on soil acid buffering capacity and organic carbon components were analyzed.ResultRelative to the control group , the addition of Fe-modified biochar prepared at 600 ℃ significantly increased soil pH by 14.76% and total organic carbon content by 160.59%, while that at 450 ℃ resulted in an increase in acid buffering capacity of 11.75%. Biochar preparation temperature and Fe-modification treatments enhanced the organic carbon contents of soil aggregates with different particle sizes in different degrees, with the greatest increase of 178.88% observed in the 0.054−0.250 mm soil aggregate. Fe-modification tended to reduce amines, hydrophobic carbon, aromatic organic matter contents, and the degree of aromaticity of soil dissolved organic carbon.ConclusionBiochar addition can significantly improve lateritic soil acid buffering and carbon sequestration capacity. However, these improvement effects are influenced by biochar preparation temperature and modification treatment.